Low-temperature corrosion performance of laser cladded WB-Co coatings in acidic environment - Han Lele; Fan Li; Chen Haiyan; Zhu Guangkuo; Qin Yujiang; Cao Qizheng (High Temperature Materials and Processes)
In this investigation, cobalt-based composite coatings with varying concentrations of spherical tungsten boride (WB) were fabricated via laser cladding technology, specifically focusing on two compositional systems: Co + 15% WB and Co + 45% WB. The electrochemical behavior of these coatings was systematically evaluated in a low-temperature hydrochloric acid environment to elucidate the influence of WB content on the corrosion resistance mechanisms of cobalt-based coatings and to reveal the electrochemical corrosion mechanisms of WB-reinforced cobalt-based coatings. Experimental results demonstrated that all coatings, including pure Co, Co + 15% WB, and Co + 45% WB, exhibited distinct passivation behavior in 0.5 mol·L−1 HCl solution. The passivation range for WB-containing coatings was predominantly observed between −0.1 V and 0.2 V. Comparative analysis revealed that the Co + 15% WB coating exhibited the most favorable corrosion resistance properties, characterized by the highest corrosion potential and the lowest corrosion current density (i corr). Furthermore, this coating composition demonstrated superior passive film resistance, charge transfer resistance (R ct), and film resistance (R f), indicating optimal protective performance in acidic environments. In contrast, the EH40 substrate exhibited significant corrosion susceptibility in acidic solutions, with the corrosion process primarily dominated by anodic dissolution. These findings provide valuable insights for the design and optimization of corrosion-resistant coatings used in marine vessels operating in corrosive acidic environments.